Social - Welfarestate in Perspective of Labour Law: Review of Asean Constitution - Icuk Rangga Bawono; Kuat Puji Prayitno (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
The welfare state in the concept of Labours cannot be covered only in scope of one state only, but also to comparation by the other countries. In order to strengthen of cooperation between asean community, we should required understanding about constitutional concept  in  asean countries . The state law concept which adopted by majority nation state according with their basic typical of the country and nationality (such as social structure and norms). To compare about welfare- labours need  more  significant idea in nationality and state. This research is prior to explain about the extent of content (recognition of state obligations which recognized on state constitution of the asean countries), using  juridical normative methodology, with emphasises from the comparison of the constitution among countries, democracy, and nomocracy. In the end, this research describe how  important if  we ask social welfare for labours concept concept (in each manuscript) to the body of constitution, and also including to found “the living constitution” in ASEAN countries. The approach method used the doctrinal legal research, including historical approach.